Neonatal End-of-Life Symptom Management - Cortezzo, DonnaMaria E.; Meyer, Mark (Frontiers in Pediatrics, 2020)
Abstract Purpose of review Despite advances in technology and treatment options, over 15,000 neonates die each year in the United States. The majority of the deaths, with some estimates as high as 80%, are the result of a planned redirection of care or comfort measures only approach to care. When curative or life-prolonging interventions are not available or have been exhausted, parents focus on preserving quality of life and eliminating needless suffering. Parents hope their child will have a peaceful death and will not feel pain. A significant component of end-of-life care is high quality symptom evaluation and management. It is important that neonatal providers are knowledgeable in symptom management to address common sources of suffering and distress for babies and their families at the end-of-life (EOL). Recent findings Medically complex neonates with life-threatening conditions are a unique patient population and there is little research on end-of-life symptom assessment and management. While there are tools available to assess symptoms for adolescents and adults, there is not a recognized set of tools for the neonatal population. Nonetheless, it is widely accepted that neonates experience significant symp-toms at end-of-life. Most commonly acknowledged manifestations are pain, dyspnea, agitation, and secretions. In the absence of data and established guidelines, there is variability in their clinical man-agement. This contributes to provider discomfort and inadequate symptom control. Summary End-of-life symptom assessment and management is an important component of neonatal end-of-life care. While there remains a paucity of studies and data, it is prudent that providers adequately man-age symptoms. Likewise, it is important that providers are educated so that they can effectively guide families through the dying process by discussing disease progression, physical changes, and providing empathetic support. In this review, the authors make recommendations for nonpharmaco-logical and pharmacological management of end-of-life symptoms in neonates.